Notions of combinatorial analysis in basic education: interdisciplinary activities - Reinaldo Amirato Dias; Adriano Vargas Freitas; Eline das Flores Victer (Educação Matemática Debate, 2017)
The article presents part of research involving analyzes on the use of interdisciplinary educational practices. We are looking for ways to increase the quality of the teaching and learning process. We emphasize for this study the concepts of combinatorial analysis in basic education. We consider that interdisciplinarity is one of the ways of articulating the learning process with students' daily lives. Thus the process becomes more meaningful and challenging for the student. We present three proposals for activities that can be used in the classroom in an interdisciplinary way. They promote debate, encourage research, and facilitate the construction of the knowledge involved.